Early works - Richardson, Samuel 1689-1761 (Cambridge University Press, 2012)
This is the first edition to assemble all of the earliest known works by Samuel Richardson (1689-1761), one of the most influential authors in the English tradition. Richardson's exercises in conduct-writing, religious controversialism, anti-theatrical polemic, occasional verse, literary criticism - and his popular and surprisingly revealing edition of Aesop's Fables - resonate throughout his later work while claiming ample legitimacy of their own. Readers familiar with only Pamela, Clarissa and Sir Charles Grandison will gain a fresh appreciation of the genesis of and the historical and cultural complexities at work in these famous novels, and readers new to Richardson will encounter an agile writer who invites closer consideration. A lengthy introduction situates the constituent works in Richardson's career as well as in the period more broadly, and the extensive textual apparatus records the bibliographical histories of the texts and their treatment by their present editor
Title from publisher's bibliographic system (viewed on 30 Jun 2022)
Machine generated contents note: General editors' preface; Acknowledgements; Chronology; List of abbreviations; General introduction; Textual introduction; The Apprentice's Vade Mecum (1733); A Seasonable Examination of the Pleas and Pretensions (1735); Verses from The Gentleman's Magazine (1736); Preface to Aubin, A Collection of Entertaining Histories and Novels (1739); Aesop's Fables (1739); Letters Written to and for Particular Friends (1741); Six Original Letters upon Duelling (1765); Appendix. The Infidel Convicted (1731); Emendations; Word-division; Bibliographical descriptions of early editions; Explanatory notes; Index